2006
DOI: 10.1111/j.1444-2906.2006.01287.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of seaweeds on histamine release from rat basophile leukemia cells (RBL-2H3)

Abstract: The effects of 80% methanol extracts from frozen samples of 41 macroalgae and one sea grass collected in the Ise-Shima region of Japan were investigated on histamine release from rat basophile leukemia cells (RBL-2H3) sensitized with antidinitrophenyl (DNP) IgE and stimulated with DNP-BSA. Of the 21 brown algae, five green and 15 red algae, and one sea grass tested, only extracts from seven brown algae suppressed histamine release from RBL cells, as determined by highperformance liquid chromatography (HPLC) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 27 publications
1
31
0
Order By: Relevance
“…Our study has shown that the total phenolic content was high in the EtOH extract of C. japonica. This finding of high phenolic and low carbohydrate content in red algae is consistent with previously published results for brown algae [27].…”
Section: Discussionsupporting
confidence: 82%
“…Our study has shown that the total phenolic content was high in the EtOH extract of C. japonica. This finding of high phenolic and low carbohydrate content in red algae is consistent with previously published results for brown algae [27].…”
Section: Discussionsupporting
confidence: 82%
“…These papers reported the anti-allergic and anti-inflammatory effects of polysaccharides (Asada et al, 1997;Maruyama et al, 2005), fatty acids (Ishihara et al, 1998) and phlorotannins (Li et al, 2008;Shibata et al, 2003;Shin et al, 2006). During our studies on the biological activities of algae, we found that an 80% methanol extract of Eisenia arborea (Phaeophyta) has an anti-allergic effect (Sugiura et al, 2006b) and that a dry powder of the alga shows a strong anti-allergic effect on Brown Norway rats, a model strain (Sugiura et al, 2008a(Sugiura et al, , 2008b. The active compounds were identified as six phlorotannins (Fig.…”
Section: Introductionmentioning
confidence: 80%
“…RBL-2H3 cells (Bursumian et al, 1981) provided by the Japanese Collection of Research Bioresources (JCRB0023, Ibaraki, Osaka, Japan) were cultured in Eagle's Modified Essential Medium (EMEM, MP Biomedicals Inc., Illkirch, France) as described in a previous report (Sugiura et al, 2006b). The cells were transferred every 4 or 5 days by trypsinization with a medium change between the transfers until they attained confluence.…”
Section: Rbl-2h3mentioning
confidence: 99%
“…Their sensory characteristics would be suitable as an additive to coffee. In addition, phlorotannins have various biological activities, such as antioxidative (Zou et al, 2008), anti-inflammatory , antibacterial , and antiallergic (Sugiura et al, 2006) effects. Therefore, HP-PRT may be a good additive for the preparation of coffee products without an arousal effect.…”
Section: Resultsmentioning
confidence: 99%